Overweight and obesity and associated factors among medical representatives in Kathmandu valley - Upadhyay-Dhungel, K.; Adhikari, Bigyan (Janaki Medical College Journal of Medical Science, 2019)
Background and Objectives: Overweight/obesity is rising problem both in developed and developing countries. This condition is important because it can lead to many chronic health conditions and is responsible for both morbidity and mortality. Medical Representatives (MRs) is one of those jobs which require minimum physical activity with good salary. MRs spends most of the day time meeting doctors of different locations. These factors make them vulnerable to overweight/obesity. Material and Methods: This study is cross sectional study in Kathmandu Valley. MRs of different company were the part of this study. Anthropometric measurements weight and height were used to calculate BMI and BMI was used to classify whether individual was normal or overweight/obesity. Semi-structured questionnaire was used to assess dietary and other lifestyle factors. Data were analyzed in SPSS to find out relationships between different factors and overweight/obesity. Results: The prevalence of overweight/obesity was found to be 64.93%. Men were significantly more overweight/obese than women. Age, Income and most of the dietary/lifestyles factors were found to be significant with overweight/obesity. Conclusion: Prevalence of overweight/obesity among MR was found to be high. MR job can be considered vulnerable to overweight/obesity because of alteration in many dietary and lifestyle factors.